2019
DOI: 10.12688/f1000research.15170.3
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Hand Foot Mouth Disease in Bangladeshi Children- First Report of Rapid Appraisal on Pocket Outbreak: Clinico-epidemiological Perspective Implicating Public Health Emergency

Abstract: Background: Hand, foot and mouth disease (HFMD) is a common contagious disease among children under 5 years, particularly in the Asia-Pacific-region. We report a localized outbreak of childhood HFMD for the first time from Bangladesh, diagnosed only based on clinical features due to lack in laboratory-diagnostic facilities. Methods: Following the World Health Organization’s case-definition, we conducted a rapid-appraisal of HFMD among all of the 143 children attending Pabna Medical College and General Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Clinical manifestations include fever, skin eruptions on the hands and feet, and vesicles in the mouth [ 56 ]. Two enteroviruses associated with HFMD were evaluated in this study: CA16, which causes self-limiting HFMD, and EV71 which can cause HFMD with neurological complications and fatality [ 57 ]. There are currently no effective antiviral drugs or vaccines available, and existing treatments are symptom-based with little efficacy, especially against EV71 [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Clinical manifestations include fever, skin eruptions on the hands and feet, and vesicles in the mouth [ 56 ]. Two enteroviruses associated with HFMD were evaluated in this study: CA16, which causes self-limiting HFMD, and EV71 which can cause HFMD with neurological complications and fatality [ 57 ]. There are currently no effective antiviral drugs or vaccines available, and existing treatments are symptom-based with little efficacy, especially against EV71 [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many children with extremely severe HFMD die before a definitive diagnosis. There are no effective and reliable methods and tools for diagnosing ( Li et al, 2014b ; Hossain Khan et al, 2018 ). A study has shown that patients with different HFMD conditions express a specific type of exosomal miRNA profile ( Jia et al, 2014 ).…”
Section: Application Of Stem Cells-derived Exosomes In Orodental Infectionsmentioning
confidence: 99%
“…Though a study done in northern Bangladesh 16 showed May and September-October as peak season for HFMD but meteorological variables affecting incidence of HFMD is not known in Dhaka, Bangladesh. This study was done to see the impact of meteorological factors like temperature, rainfall and humidity on the incidence of HFMD in Dhaka city.…”
Section: Introductionmentioning
confidence: 98%